Literature Review Penatalaksanaan Ketidaknyamanaan pada Ibu Hamil Trimester III - Fatmasari, Nawang; Ardila; Nur Jannah, Siti; Anggraenii, Anggit; Sapitri, Wiwik Sapitri; Windi Fitriyani; Hapsari Windayati (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2023)
Pregnancy is the meeting between ovum and sperm, which causes physical and mental changes. Pregnant women often experience problems such as frequent urination 50%, vaginal discharge 15%, constipation 40%, flatulence 30%, swelling in the legs 20%, cramps in the legs 10%, headaches 20%, striae gravidarum 50%, hemorrhoids 60 %, shortness of breath 60%, and back pain 70%. Overcome discomfort by doing appropriate relaxation activities, such as yoga, pregnancy exercises, abdominal stretching kinesio tapping, warm water immersion therapy, soaking in boiled galangal water, warm and cold water compresses. The aim of this literature review is to overcome third trimester discomfort in pregnant women. The method used in preparing this research is Literature Review by analyzing a predetermined number of articles. This research consists of 14 articles which will be analyzed using article selection techniques using article criteria used in accordance with the research objectives. The results of the literature review of the 14 articles show that pregnant women who experience third trimester discomfort can reduce complaints from pregnant women. Conclusions from the management of discomfort in the third trimester of pregnancy are very relevant for dealing with discomfort in the third trimester of pregnancy. This is very useful because with this management, it is hoped that pregnant women can overcome discomfort in the third trimester of pregnancy.   Abstrak Kehamilan adalah pertemuan antara ovum dan sperma, yang menyebabkan perubahan fisik dan mental. Adaptasi fisiologi ibu hamil pada Trimester III seperti sering buang air kecil 50%, keputihan 15%, konstipasi 40%, perut kembung 30%, bengkak pada kaki 20%, kram pada kaki 10%, sakit kepala 20%, striae gravidarum 50%, hemoroid 60%, sesak nafas 60%, dan sakit punggung 70%. Mengatasi ketidaknyamanan dengan melakukan aktivitas relaksasi yang tepat, seperti yoga, senam hamil, abdominal stretching kinesio tapping, terapi rendam air hangat, rendaman air rebusan kencur, kompres air hangat dan dingin.  Tujuan dari literature review ini yaitu untuk mengetahuii  ketidaknyamaanan trimester III pada Ibu Hamil dengan non farmakologi.Literature Review  terdiri dari 14 artikel yang di analisis dengan kata kunci ibu hamil, penatalaksanaan trimester III. simpulan dari penatalaksanaan ketidaknyamanaan ibu hamil trimester III itu gerakan yoga, senam hamil, abdominal stretching kinesio tapping, terapi rendam air hangat, rendaman air rebusan kencur, kompres air hangat dan dingin . saran untuk mengurangi ketidaknyamanan pada nyeeri punggung, sesak nafas, nyeri tungkai, dan odema.